PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN JASA GOJEK DI KOTA MALANG - Mohammad Maskan; Bambang Soepeno; Rulirianto Rulirianto (Politeknik Negeri Malang, 2019)
The purpose of this study will examine how the influence of service quality and price on the decision to buy a taxi service in the city of Malang. The research used is quantitative research. The research method used was survey research. The number of questionnaires collected in this study totaled 50 Gojek users. The analytical method used is multiple regression. Meanwhile, to test the hypothesis used the F test and t test. The results showed that there was a significant influence between the variable service quality (X1) and price (X2) on the purchasing decision of Gojek services in Malang City (Y). This is indicated by the results of multiple regression calculations, Y = 2.177 + 0.356 X1 + 0.215 X2 Service quality and price variables are able to be explained by the variable purchasing decisions of Gojek services in Malang by 15%.